The teenage twist: Meckel’s diverticulum masquerading as a closed loop small bowel obstruction - Vishnu, R.; Ravikumar, Sumathi; Bernard, F. Grey; Deepika (International Surgery Journal, 2025)
Meckel’s diverticulum is a congenital anomaly that is often clinically silent but can present with life-threatening complications. In adolescents, its presentation as acute intestinal obstruction due to a closed loop is extremely rare and diagnostically challenging. We report a case of a 15-year-old male who presented with acute abdominal pain, vomiting, and distension. Clinical and imaging features suggested closed-loop small bowel obstruction. Emergency exploratory laparotomy revealed a gangrenous segment of the distal ileum and a Meckel’s diverticulum associated with dense adhesions. The patient underwent resection of the gangrenous ileum and cecum with end ileostomy. Postoperative recovery was uneventful, histological examination revealed coagulative necrosis with ectopic pancreatic tissue in Meckel’s diverticulum and he was discharged in a stable condition. This case emphasizes the importance of considering Meckel’s diverticulum in the differential diagnosis of intestinal obstruction in adolescents, especially in the absence of previous abdominal surgeries. Early surgical intervention is essential to prevent ischemic complications and optimize outcomes.